Life cycle assessment of Australian sugarcane products with a focus on cane processing. - Renouf, Marguerite Anne
Purpose This work generates attributional life cycle assessment (LCA) results for products produced from Australian sugarcane-raw sugar, molasses, electricity (from bagasse combustion), and ethanol (from molasses). It focuses on cane processing in sugar mills and is a companion to the work presented in (Renouf et al. 2010), where the focus is on cane growing. This work also examines the preferred approoach for assigning impacts to the multiple products from cane processing, and the influence that variability in cane growing has on the results. Method Initially, global warming potentials were generated for a range of cane processing models, using economic allocation (EA), mass allocation (MA) and system expansion (SE). A preferred approach was identified and applied to generate results for a wider set of impact categories based on the Impact 2002+ method. Uncertainty in the results due to cane growing variability was assessed using Monte Carlo analysis and compared with the results of substitute products to determine the significance of the variability. Results While the generation of results using SE was appealing for assessing the determinng product (raw sugar), it was found to be less valid for the co-products (molasses, electricity and ethanol). Results could be generated more consistently across all products using allocation. MA was found to be best suited to sugarcane products, whereas EA posed some problems. The uncertainty due to variability in sugarcane growing was found to be significantly higher than that of substitute products. Conclusions and recommendations LCA results for sugarcane products are influenced by (1) the nature of cane processing system, (2) variability in sugarcane growing and (3) the approach taken for assigning impacts to be multiple products from sugarcane processing. The first two factors imply that results should be specific to the cane growing region and the cane processing used to produce them. In relation to the latter issue, for generating attributional LCA results that are consistent across all sugarcane products, the recommended approach is to use mass allocation (with energy allocation for bagasse combustion and cogeneration).
Keywords: Allocation; Electricity; Ethanol; Molasses; Sugar; System expansion; Variability